Analisis Objek Daya Tarik Wisata Favorit Berdasarkan Jumlah Pengunjung Di Daerah Istimewa Yogyakarta - Yulianto, Atun (JURNAL MEDIA WISATA: Wahana Informasi Pariwisata, 2017)
Besides known as the city with the title of the center of struggle, cultural and educational center, Daerah Istimewa Yogyakarta is also known as a city that has beautiful natural scenery, cultural and traditional arts that are still sustainable until now. Daerah Istimewa Yogyakarta (DIY) has various facilities of tourism with adequate quality and spread across five districts that is Sleman, Kulon Progo, Gunung Kidul, Bantul and Kota Yogyakarta. This study aims to determine the object of tourist attraction in Daerah Istimewa Yogyakarta which is a favorite of tourists based on the number of visitors range from 2011 to 2015. The research method used is descriptive qualitative supported quantitative data to provide a mathematical picture of the three objects of tourist attraction what is the most dominant visited by tourists. The results of this study indicate the order based on the number of visitors, namely Parangtritis Beach occupies the first position, followed by Prambanan Temple and Gembira Loka zoo become the favorite tourist attraction object of visitors.Suggestions in this study is the need for comparative study and adoption of road map of strategic planning and operational in preparing tourism marketing strategy to bring more tourists to the manager of tourist attraction object which is still few number of visitors.